The challenges and prospects for carbon pricing in Europe - Alex Barnes (The Oxford Institute for Energy Studies, 2021)
Carbon pricing is seen as an essential tool of decarbonisation, and hence of meeting net zero emissions targets by 2050. Both the EU 27 and the UK have committed to reaching net zero by 2050, and include carbon pricing as part of their strategy. The paper provides an overview of the current status of carbon pricing in the EU 27 + UK, and coming policy developments such as the introduction of a UK Emissions Trading System (ETS), now that the UK has left the EU, reform of the EU ETS, and the EU's proposal for a Carbon Border Adjustment Mechanism, more colloquially known as a carbon border tax. The literature on carbon pricing is vast, and many of the issues, such as design of carbon pricing mechanisms, are complex. It would not be possible to cover all the issues in depth in a short paper; rather the aim is to review the recent developments of carbon pricing in a European context and to provide a platform for further, more detailed research on key issues identified in the conclusions of the paper. The paper is structured as follows. Section II gives a brief overview of what is meant by carbon pricing. Section III looks at current carbon pricing in the EU 27 including the EU Emissions Trading System and other carbon pricing mechanisms. Section IV covers carbon pricing in the UK, including the new UK Emissions Trading System. Section V looks at future opportunities and challenges for European carbon pricing. Section VI considers future topics for research, and the implications for natural gas in Europe.
Keywords: 330; Carbon Border Adjustment Mechanism; Carbon pricing; decarbonisation; Emissions Trading System; Energy Taxation; EU ETS; net-zero; UK ETS